VBA (Visual Basic for Applications) Based Learning Media Development in Accounting Practice Learning - Ulfa, Agfia Fauziatul; Laily, Nujmatul (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
This research aims to produce learning media products based on Excel VBA (Visual Basic for Applications) in accounting practice learning. This research used the R&D method with the ADDIE model, namely: Analyze, Design, Develop, Implement, and Evaluate. The subjects in this research were Grade XI Financial and Institutional Accounting students at SMK Negeri 2 Kediri. The results showed that the Excel VBA-based learning media showed the media’s feasibility with validation test results by media expert of 100% and material expert of 90.87% and feasible category. In addition, the results of validation test on field practitioners (teachers) and students showed practicality and feasibility of the application of 98.61% and 93.25% respectively for accounting practice learning in Accounting Vocational Schools. Therefore, the presence of Excel VBA application as a learning medium developed is very effective and suitable for use in Accounting Vocational Schools.